Health promotion preparedness for health crises – a 'must' or 'nice to have'? Case studies and global lessons learned from the COVID-19 pandemic. (June 2021) - Levin-Zamir, Diane; Sorensen, Kristine; Su, Tin Tin; Sentell, Tetine; Rowlands, Gillian; Messer, Melanie; Pleasant, Andrew; Saboga Nunes, Luis; Lev-Ari, Shahar; Okan, Orkan
The current COVID-19 pandemic has exposed missing links between health promotion and national/global health emergency policies. In response, health promotion initiatives were urgently developed and applied around the world. A selection of case studies from five countries, based on the Socio-Ecological Model of Health Promotion, exemplify 'real-world' action and challenges for health promotion intervention, research, and policy during the COVID-19 pandemic. Interventions range from a focus on individuals/families, organizations, communities and in healthcare, public health, education and media systems, health-promoting settings, and policy. Lessons learned highlight the need for emphasizing equity, trust, systems approach, and sustained action in future health promotion preparedness strategies. Challenges and opportunities are highlighted regarding the need for rapid response, clear communication based on health literacy, and collaboration across countries, disciplines, and health and education systems for meaningful solutions to global health crises.